Editorial - Stefania De Gregorio; Mariangela De Vita (Vitruvio: International Journal of Architectural Technology and Sustainability)
Editorial VITRUVIO - International Journal of Architectural Technology and Sustainability, Volume 8, Issue 2 (2023)